Fiscal and Monetary Policy Synergy In The Context of National Economic Recovery After The Covid-19 Pandemic - Wartoyo, Wartoyo; Amalia, Tia; Fajriyatin, Fajriyatin; Haida, Nur (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
The COVID-19 virus is a global pandemic or disaster, forcing all countries to overcome health crises and a number of other crises such as economic crises. This study aims to determine the condition of Indonesia's economic growth both during the pandemic and the latest conditions and find out how the implementation process of synergy between fiscal and monetary policies in an effort to overcome the Covid-19 pandemic and post-pandemic. This research uses a qualitative approach with the type of literature research. Literature research itself obtains its data sources by collecting data sourced from books, journals, notes or reports related to the formulation of the problem to be studied. The results of the study convey that the impact of fiscal and monetary policies pursued by the Indonesian government can be said to be successful. This can be proven by Indonesia's economic condition, which experienced a slowdown at the beginning of the pandemic, changing towards positive growth at the end of 2021 to 2022, meanwhile, in terms of monetary policy, namely maintaining economic stability, strengthening macroprudential policy, accelerating payment system digitalization, strengthening inclusive economic-financial policy, and strengthening international policy.